Association between the composite dietary antioxidant index and infertility: the national health and nutrition examination survey 2013-2020 - Yang Shen; Zhanwang Tan; Zibo Duan; Jingxiao Chen; Zijiao Yang; Xiaohua Lin (BMC, 2024)
Abstract Background The use of antioxidant-rich foods to treat female infertility has received significant attention in recent years. The aim of this study was to investigate the potential correlation between the composite dietary antioxidant index (CDAI) and female infertility. Methods The participants in the cross-sectional data were women between the ages of 20 and 45 who had complete CDAI-related data and infertility information, which were taken from the National Health and Nutrition Examination Survey (NHANES) conducted between 2013 and 2020. The independent association between CDAI and infertility was investigated using multivariate logistic regression analysis. Trends between the two variables were examined using smoothed curve fitting, and subgroup analysis and interaction tests were conducted. Results The prevalence of infertility was 12.57% of the 3,259 participants included in the study; individuals in higher CDAI quartiles tended to have a lower percentage of infertility. The risk of infertility was 44% lower among individuals in the highest quartile of the CDAI compared to those in the lowest quartile (OR = 0.56, 95%CI: 0.36-0.85, P = 0.0072), and the test for trend was also significant (P for trend = 0.0235). Smoothed curve fitting showed a negative non-linear relationship between CDAI and infertility. Subgroup analysis and interaction tests showed that there was an interaction of BMI in the relationship between CDAI and infertility risk (P for interaction = 0.0497) and that education, PIR, marital status, smoking status, hypertension, diabetes, age at menarche, ever having been treated for pelvic infection, ever having used female hormones, and ever been pregnant had no significant dependence on this negative association (all P for interaction > 0.05). Conclusion There was a negative non-linear correlation between CDAI and infertility among reproductive-aged women in the US. The risk of infertility may be reduced by increasing the intake of antioxidant-rich foods.